Obstacles to the lack of a standard Kurdish dictionary and the steps of writing a dictionary Dot dictionaries and the like as e.g - Khader, Asst. L. Hashem Amin (Sulaimani Journal for Humanities, 2023)
Throughout history، culture has been one of the reasons why many unknown things are known to humans. Of course، the dictionary of any language consists of the information of the dictionary of the human mosquito، and the place of the dictionary in the sciences is part of the new science of linguistics، on the other hand، we can count the dictionary as an important title and source of words، terms، and linguistic linguistics، but the lack of a Kurdish-Kurdish/standard dictionary، such as the key to the lock of the language، keeps it closed، because the language is constantly changing، and the words are dying، and the words are added to it and need to be renewed. Only the dictionary can preserve and preserve all these words، and this dictionary can explain the root of many of the terms that contain more meaning and a variety of meanings، the dictionary informs all the speakers of the language about the root and origin of the word of the language، and the language is the assistant of this aspect to the dictionary and constantly tries to improve the dictionary of words even by bringing in foreign words and adapting it to the rules of language. Also، the important aspect of the dictionary in this study is to mention the total number of (510) dictionaries issued during 1787-2022، but in this research، only (50) Kurdish dictionaries and dictionaries and the opening of the historical side of the Kurdish-Kurdish dictionary begins with the dictionary of the point and is referred to as more than ten Kurdish-Kurdish dictionaries until now، because this is a small and specific study that can be done in the future. The purpose of teaching and some of them are written for commercial purposes to learn the basics of a dialect، but none of these dictionaries have been implemented in a scientific، constitutional and linguistic framework and have not been a good material for scientific research. In this study، we try to present all the points، shortcomings and weaknesses in the field of Kurdish dictionary writing and the challenges facing the lack of standard Kurdish dictionaries.